Report on Scaling Partners Network: Action Plan for Fertilizer Advisory Scaling Strategy: Fertilizer Ethiopia/HighMix Gvt Eth Use Case. Hyderabad, India: ICRISAT. - Desta, Gizaw; Tigabie, Abio; Legesse, Gizachew; Henok, Desalegn; Getachew, Agegnehu (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Towards realizing Agronomy Science Scaling and Acceleration Partnerships (ASSAP objectives, currently, two levels of scaling partner platforms are functioning. First, the national DST harmonization coordination platform (i.e., established in Nov 2023) operates through seven functional modules (Fig 1) involving national partners. The platform plays the role of decision-making and facilitates linkage between science (CG and NARES) and demand (government) and leading the harmonization of innovation packages. This platform has a governance structure co-chaired by EIAR and MoA including a core/executive team from more than 20 key partners at the national level. The other modules dealt with the harmonization of soil and agronomy data, tools, and delivery mechanisms. As a result of this collaborative partnership, a harmonized fertilizer advisory is being validated through NARES and the support of the CG centers.